Geographic distribution of COPD prevalence in the world displayed by Geographic Information System maps - Ignacio Blanco; I. Diego; Patrícia Bueno; Francisco Maldonado; Marc Miravitlles (2019)
The global prevalence of COPD is 13.1%, ranging from 11.6% in Oceania to 13.9% in Africa. With the aid of GIS technology, a global map of prevalence of COPD has been obtained including areas without real data.http://bit.ly/2HRWfK7